Hands-on Microsoft Windows XP Professional - Adamson, Jay (Thomson Course Technology, 2003)
The Hands-on Windows XP Professional and Server 2003 Networking Series is designed for the instructors and students interested in the new Microsoft Windows XP Professional and Server 2003 networking technology, but not immediately interested covering the MCSE/MCSA Exam objectives. These practical books provide complete coverage of Windows XP Professional and Server 2003 networking concepts in a concise manner, and include ample opportunity for students to get practical experience with hands-on exercises and real-world scenarios distributed throughout the chapters